1980
DOI: 10.1111/j.1471-4159.1980.tb11253.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Studies of the Mesolimbic Dopaminergic Pathway: Somatodendritic Mechanisms and GABAergic Neurones in the Rat Ventral Tegmentum

Abstract: The rat ventral tegmentum (containing dendrites and somata of mesolimbic neurones) contained 1.3 pglg of dopamine, which was reduced to 40% of the control level by reserpine. Slices of ventral tegmentum were able to accumulate and release (elevated potassium or protoveratrine A) exogenous [3H]dopamine. In parallel studies the uptake mechanism in ventral tegmentum w a s shown t o be virtually identical t o t h e nerve terminal uptake of ["Hldopamine by slices of nucleus accumbens. The release of [RH]dopamine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…3H-DA uptake was measured after incubation of the cells with 3H-DA, 10 • 10 -gM, in the presence of pargyline, 10 5 M, and ascorbic acid, 10 -3M, at 37~ for 30 rain. Non-specific uptake/ binding was calculated at 0~ and/or in the presence of 10 -SM mazindol (Beart and McDonald, 1980). Proteins were measured according to Bradford (1976).…”
Section: Studies In Fetal Mid Brain Rat Neuronsmentioning
confidence: 99%
“…3H-DA uptake was measured after incubation of the cells with 3H-DA, 10 • 10 -gM, in the presence of pargyline, 10 5 M, and ascorbic acid, 10 -3M, at 37~ for 30 rain. Non-specific uptake/ binding was calculated at 0~ and/or in the presence of 10 -SM mazindol (Beart and McDonald, 1980). Proteins were measured according to Bradford (1976).…”
Section: Studies In Fetal Mid Brain Rat Neuronsmentioning
confidence: 99%
“…TH activity was measured according to the rate of accumulation of DOPA after inhibition of its decar-boxylation by NSD 1015, 100 mg/liter, for 30 min (Carlsson et al, 1972). High affinity 3H-DA uptake was evaluated according to Beart and McDonald (1980) and choline acetyltransferase (CAT) activity according to Galea and Estrada (1991).…”
Section: Studies With Neuroblastoma Cells Nb69mentioning
confidence: 99%
“…Accordingly, several lines of evidence have shown that there is functional expression of DAT in this region. Autoradiographic uptake experiments, for example, have demonstrated the presence of sodium-dependent dopamine uptake in the VTA that is sensitive to DAT inhibitors (Beart et al, 1979;Beart and McDonald, 1980). In addition, the local application of DAT-inhibiting drugs in the VTA has been shown to increase extracellular levels of dopamine (Kalivas and Duffy, 1991;Chen and Reith, 1994), leading to inhibition of dopaminergic cell firing in this region (Einhorn et al, 1988).…”
Section: Introductionmentioning
confidence: 99%